2013
DOI: 10.4028/www.scientific.net/amr.832.500
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibre Network Rooted from the Alkaline Peroxide Treatment of Oil Palm Empty Fruit Bunches

Abstract: The increasing popularity of the oil palm empty fruit bunches (EFB) as a source of non-wood fibre has prompted a variety of research on processing and utilisation of the material. In an attempt to define the characters, reusability and end-of-life, oil palm EFB was processed by the alkaline peroxide variable treatment (APVT) systems. Low synergy between alkaline peroxide (AP) chemical and mechanical fibrillation through fibrillation (CMR synergy) revealed the yield of segments of EFB vascular bundles while hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…3c, are unhelpful in promoting sheet strength. These are elements responsible to the acclaimed 'fiber coalescence' commonly encountered on the surface of EFB pulp handsheets of tensile index above 15 Nm/g (Ghazali et al 2011;Dermawan and Ghazali 2011). By masking of individual fiber strands and promoting sheet cohesion, the pulp network appears smoother.…”
Section: Characterization Of Fines In Screened Pulpmentioning
confidence: 99%
See 1 more Smart Citation
“…3c, are unhelpful in promoting sheet strength. These are elements responsible to the acclaimed 'fiber coalescence' commonly encountered on the surface of EFB pulp handsheets of tensile index above 15 Nm/g (Ghazali et al 2011;Dermawan and Ghazali 2011). By masking of individual fiber strands and promoting sheet cohesion, the pulp network appears smoother.…”
Section: Characterization Of Fines In Screened Pulpmentioning
confidence: 99%
“…While flakes were found to be of less value (Luukko and Paulapuro 1999;Subramanian et al 2008), fibrillar structures were found to render paper density, less of solid-air extension and therefore improved optical qualities. Early attempts of APP of EFB not only showed encouraging effects of fines on paper strength (Ghazali et al 2011) but also 70% improvement in refining discharge clarity, which is important in reduction of total suspended solids (TSS) in used process water. At the present level of knowledge, TSS reduction is achieved by backwash filtration technology, adopted in the whitewater closed-loop systems where reuse of water in the water-intensive industry is made more efficient (Shukla et al 2012).…”
Section: Introductionmentioning
confidence: 99%